Skills transfer to sinus surgery via a low‐cost simulation‐based curriculum. Issue 4 (11th January 2018) - Harbison, R. Alex; Dunlap, Jennifer; Humphreys, Ian M.; Davis, Greg E.
Abstract : Background: Surgical skill development outside the operating room aims to improve technique and subsequent patient safety. The purpose of this study was to evaluate the correlation between technical and cognitive skills with cadaveric endoscopic sinus surgery (ESS) performance and change in ESS performance before and after implementation of a dedicated ESS simulation‐based and knowledge‐based curriculum. Methods: A before‐after study design was implemented among 10 medical students and 10 junior otolaryngology residents. Participants completed a knowledge‐based, multiple‐choice ESS pretest and watched an ESS prosection video. Participants performed 9 tasks on a previously validated low‐cost, low‐technology, nonbiologic sinus surgery task trainer followed by cadaveric maxillary antrostomy and anterior ethmoidectomy. Participants then completed a simulation‐based and knowledge‐based ESS curriculum followed by a repeat cadaveric maxillary antrostomy and anterior ethmoidectomy. Performance was graded with a 5‐point global rating scale (GRS) and a 5‐point ESS‐specific checklist. Results: We observed a stronger correlation between the multiple‐choice, knowledge‐based, ESS pretest scores and cadaveric ESS GRS score ( r = 0.73) than between task trainer performance and cadaveric ESS GRS score ( r = 0.43). We also noted a significant increase in precurriculum vs postcurriculum mean ± standard deviation (SD) cadaveric ESS checklist scores for both medical students (1.18 ± 0.25 vs 2.58 ± 0.57; p = 0.0002) and residents (2.09 ± 0.78 vs 2.88 ± 0.54; p = 0.023). The greatest improvements for residents were in performance of uncinectomy, enlargement of maxillary os, and identification of the bulla. Conclusion: These findings provide evidence supporting the use of ESS training curricula outside the operating room.